OUTDOOR LEARNING BERBASIS KEGIATAN BERKEBUN UNTUK PERKEMBANGAN KOGNITIF, AFEKTIF, DAN PSIKOMOTOR PADA ANAK USIA 3-6 TAHUN - Nahiyah Faraz; Gregorius Ari Nugrahanta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Gardening activities have a significant impact in supporting early childhood development in three main domains: cognitive, affective and psychomotor. This study aims to discuss more about each step of gardening activities and how it impacts on children's cognitive, affective and psychomotor aspects and examine how each step of outdoor learning activities can be an effective learning method to stimulate children's development holistically. In this case researcher used descriptive qualitative method with 2 research techniques, which is a field study in the form of observation in one of the Montessori schools in Yogyakarta and literature study to describe the impact of gardening activities on early childhood development in cognitive, affective, and psychomotor aspects. The results showed that the outdoor learning activities of gardening starting from preparing the land, planting seeds, watering and providing fertilizer, until harvesting as implemented in one of the Montessori schools in Yogyakarta turned out to provide meaningful learning experiences and also effectively meet the cognitive, affective, and psychomotor needs of children. This research is expected to be a reference for educators in innovating creative learning designs that focus on real experiences.